2023
DOI: 10.1007/s13202-023-01697-0
|View full text |Cite
|
Sign up to set email alerts
|

A review of cement sheath integrity evaluation techniques for carbon dioxide storage

Okhiria D. Udebhulu,
Yetunde Aladeitan,
Ricardo C. Azevedo
et al.

Abstract: Cement sheath integrity is a critical concern in the successful implementation of geologic carbon capture and storage (CCS) projects. Conventional ordinary Portland cement (OPC) is not thermodynamically compatible with the carbon dioxide (CO2) present in CO2 storage media. When OPC cement sheaths interact with aqueous CO2, they undergo degradation, producing calcium bicarbonate. This bicarbonate readily dissolves in the formation aquifer and can create leakage pathways, compromising the integrity of the wellbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…However, they used only computed tomography scans to evaluate cement integrity. Most recently, Udebhulu et al [43] reviewed cement sheath integrity evaluation techniques for GCS and reported that the permeability of cement is the most critical parameter for cement integrity. The reactivity of CO2 in the presence of water with cement is one of the main concerns in GCS operations.…”
Section: Introductionmentioning
confidence: 99%
“…However, they used only computed tomography scans to evaluate cement integrity. Most recently, Udebhulu et al [43] reviewed cement sheath integrity evaluation techniques for GCS and reported that the permeability of cement is the most critical parameter for cement integrity. The reactivity of CO2 in the presence of water with cement is one of the main concerns in GCS operations.…”
Section: Introductionmentioning
confidence: 99%